MG-114 First 2 years of experience of an integrated multidisciplinary clinic for adults with aortopathies in a canadian context. (4th December 2015) - Laberge, Anne-Marie; Hamamsy, Ismail El; Robb, Laura; Demers, Philippe; Poirier, Nancy; Mongeon, François-Pierre
Abstract : Background: In 2012, the Montreal Heart Institute started an integrated multidisciplinary clinic for adults referred for suspicion of Marfan syndrome or other connective tissue disorders at risk of aortic disease. A heart team (cardiologist specialised in adult congenital heart disease, heart surgeons specialised in aortic surgery) and a genetics team (medical geneticist, genetic counsellor) work side-by-side. Both teams see patients with a family history of aortic disease or systemic features of Marfan syndrome. The heart team sees patients with presumed isolated aortic disease and determines if evaluation by the genetics team is needed. Objective: Assess first two years of clinic activities. Methods: Review of clinic database and patient charts for period between May 2012 and May 2014. Results: 183 new patients were assessed, from 146 different families. Reasons for referral included suspicion of Marfan (72), Loeys-Dietz (15), or Ehlers-Danlos syndrome (8); TAAD (56); and sudden death in the family (6). All were seen by the heart team; 70 were seen by the geneticist for a dysmorphological exam. All had dedicated cardiovascular imaging in our centre. Genetic tests were ordered for 35 patients. Close links with the paediatric and prenatal genetic clinics have facilitated efficient cross-referrals: we referred eight children of our adult patients. Most importantly, we rapidly assessed three pregnant women at risk of aortic disease and eight affected parents (identified through their child) who had no active follow-up. Conclusions: Our integrated multidisciplinary approach results in efficient access to specialised cardiac and genetic assessments and rapid management when required.